Advancing interoperability of geospatial data provenance on the web: Gap analysis and strategies. (August 2018) - Jiang, Liangcun; Yue, Peng; Kuhn, Werner; Zhang, Chenxiao; Yu, Changhui; Guo, Xia
Abstract: Geospatial data provenance is a fundamental issue in distributing spatial information on the Web. In the geoinformatics domain, provenance is often referred to as lineage. While the ISO 19115 lineage model is used widely in spatial data infrastructures, W3C has recommended the W3C provenance (PROV) data model for capturing and sharing provenance information on the Web. The use of these two separate efforts needs to be harmonized so that geospatial information does not remain an isolated area on the Web. Motivated by several domain use cases, we synthesize a list of provenance questions and analyze gaps between the two models in addressing these questions. Our strategy is to enrich W3C PROV with domain semantics from the ISO 19115 lineage model by suggesting ways to bridge them. A semantic mapping between the ISO lineage model and the W3C PROV model is formalized, and key issues involved are discussed. Use cases illustrate the applicability of the approach. Highlights: Key considerations for geospatial data provenance. Gap analysis between the ISO lineage model and W3C PROV model. Semantic mapping from ISO Lineage to W3C PROV.